The relevance of piroxicam for the prevention and treatment of nonmelanoma skin cancer and its precursors - Campione E; Paternò EJ; Candi E; Falconi M; Costanza G; Diluvio L; Terrinoni A; Bianchi L; Orlandi A (Dove Medical Press, 2015)
Elena Campione,1 Evelin Jasmine Paternò,2 Eleonora Candi,3,4 Mattia Falconi,5 Gaetana Costanza,2 Laura Diluvio,1 Alessandro Terrinoni,4 Luca Bianchi,1 Augusto Orlandi2,6,7 1Department of Dermatology, 2Department of Biomedicine and Prevention, 3Department of Experimental Medicine and Surgery, University of Rome “Tor Vergata”, 4Biochemistry Laboratory IDI-IRCCS, Faculty of Medicine, University of Rome “Tor Vergata”, 5Department of Biology, University of Rome “Tor Vergata”, 6Institute of Anatomic Pathology, University of Rome “Tor Vergata”, 7Tor Vergata University-Policlinic of Rome, Rome, Italy Abstract: Piroxicam (PXM), a nonsteroidal anti-inflammatory drug, is an enolic benzothiazine and a potent member of the oxicam series. The drug suppresses the synthesis of proinflammatory enzymes, such as cyclooxygenases-1 and -2 (COX-1 and 2), downregulates the production of prostaglandins (PGs) and tromboxanes, and inhibits polyamines production by blocking ornithine decarboxylase induction involved in nonmelanoma skin carcinogenesis. In addition, PXM is able to induce tumor cell apoptosis and suppresses metalloproteinase 2 activities. Skin carcinogenesis is a multistep process in which the accumulation of genetic events leads to a gradually dysplastic cellular expression, deregulation of cell growth, and carcinomatous progression. COX-1 upregulation plays a significant role in PG and vascular epidermal growth factor production supporting tumor growth. Increased level of PGs in premalignant and/or malignant cutaneous tumors is also favored by upregulation of COX-2 and downregulation of the tumor suppressor gene 15-hydroxy-prostaglandin dehydrogenase. Chemoprevention can be a hopeful approach to inhibit carcinoma occurrence before an invasive tumor develops. The chemopreventive effect of nonsteroidal anti-inflammatory drugs on nonmelanoma skin cancers has been established. In this study, we highlighted the different modalities of action of PXM on the pathogenesis of nonmelanoma skin cancer, analyzing and evaluating binding modes and energies between COX-1 or COX-2 and PXM by protein–ligand molecular docking. Our clinical experience about the local use of PXM on actinic keratoses and field cancerization is also reported, confirming its efficacy as target therapy. Keywords: COXs inhibitor, actinic keratosis, tumor progression, binding mode